Pharmacological Inhibition of Serine Proteases to Reduce Cardiac Inflammation and Fibrosis in Atrial Fibrillation - Coppini, Raffaele; Santini, Lorenzo; Palandri, Chiara; Sartiani, Laura; Cerbai, Elisabetta; Raimondi, Laura (Frontiers in Pharmacology, 2019)
Systemic inflammation correlates with an increased risk of atrial fibrillation (AF) and thrombogenesis. Systemic inflammation alters vessel permeability, allowing inflammatory and immune cell migration toward target organs, including the heart. Among inflammatory cells infiltrating the atria, macrophages and mast cell have recently attracted the interest of basic researchers due to the pathogenic mechanisms triggered by their activation. This chemotactic invasion is likely implicated in short- and long-term changes in cardiac cell-to-cell communication and in triggering fibrous tissue accumulation in the atrial myocardium and electrophysiological re-arrangements of atrial cardiomyocytes, thus favoring the onset and progression of AF. Serine proteases are a large and heterogeneous class of proteases involved in several processes that are important for cardiac function and are involved in cardiac diseases, such as (i) coagulation, (ii) fibrinolysis, (iii) extracellular matrix degradation, (iv) activation of receptors (i.e., protease-activated receptors [PPARs]), and (v) modulation of the activity of endogenous signals. The recognition of serine proteases substrates and their involvement in inflammatory/profibrotic mechanisms allowed the identification of novel cardio-protective mechanisms for commonly used drugs that inhibit serine proteases. The aim of this review is to summarize knowledge on the role of inflammation and fibrosis as determinants of AF. Moreover, we will recapitulate current findings on the role of serine proteases in the pathogenesis of AF and the possible beneficial effects of drugs inhibiting serine proteases in reducing the risk of AF through decrease of cardiac inflammation and fibrosis. These drugs include thrombin and factor Xa inhibitors (used as oral anticoagulants), dipeptidyl-peptidase 4 (DPP4) inhibitors, used for type-2 diabetes, as well as novel experimental inhibitors of mast cell chymases.